Age-related decline in white matter tract integrity and cognitive performance: A DTI tractography and structural equation modeling study - Voineskos, Aristotle N. (2010)
Age-related decline in microstructural integrity of certain white matter tracts may explain cognitive decline associated with normal aging. Whole brain tractography and a clustering segmentation in 48 healthy individuals across the adult lifespan were used to examine: interhemispheric (corpus callosum), intrahemispheric association (cingulum, uncinate, arcuate, inferior longitudinal, inferior occipitofrontal), and projection (corticospinal) fibers. Principal components analysis reduced cognitive tests into 6 meaningful factors: (1) memory and executive function; (2) visuomotor dexterity; (3) motor speed; (4) attention and working memory; (5) set-shifting/flexibility; and (6) visuospatial construction. Using theory-based structural equation modeling, relationships among age, white matter tract integrity, and cognitive performance were investigated. Parsimonious model fit demonstrated relationships where decline in white matter integrity may explain age-related decline in cognitive performance: inferior longitudinal fasciculus (ILF) with visuomotor dexterity; the inferior occipitofrontal fasciculus with visuospatial construction; and posterior fibers (i.e., splenium) of the corpus callosum with memory and executive function. Our findings suggest that decline in the microstructural integrity of white matter fibers can account for cognitive decline in normal aging.